Effectiveness of Discharge Education on Postpartum Depression. Issue 3 (May 2016) - McCarter-Spaulding, Deborah; Shea, Stephen
Abstract: Purpose: To determine effectiveness of an educational intervention in reducing or preventing symptoms of postpartum depression (PPD). Study Design and Methods: English-speaking women age 18 or older with a singleton, term, healthy newborn were recruited from an 11-bed maternity unit in Southern New Hampshire. Using a quasi-experimental design, the first 120 respondents received usual care (control), and the following 120 respondents received the education (treatment) including PPD predictors, symptoms, prevention, and management. Current risk factors were measured using the Postpartum Depression Predictors Inventory-Revised (PDPI-R). Symptoms of depression were measured using the Edinburgh Postnatal Depression Scale (EPDS) at 6 weeks, 3 months, and 6 months postpartum. Two-proportion z -tests were used to determine whether the education had a significant impact on EPDS scores at each of the three follow-ups. Results: There was no significant difference in symptoms of depression as measured by the EPDS between the treatment and control group at 6 weeks, 3 months, or 6 months postpartum. However, consistent with previous studies, low socioeconomic status and a history of depression or anxiety prior to or during the pregnancy were significant predictors of PPD. Clinical Implications: Postpartum nursing discharge education did not decrease depression symptoms up to 6 months after discharge. More research is needed to determine the most appropriate timing and content of education about PPD. Many women at risk can be identified prior to birth. Education to improve literacy about PPD may need to be provided prenatally and reinforced during postpartum hospitalization and after discharge. Abstract : Postpartum depression is a serious condition that disproportionately affects women of low socioeconomic status and women with a history of prior depression or anxiety. This study evaluated efficacy of an education intervention for women during postpartum hospitalization in minimizing risk of depression at 6 weeks, 3 months or 6 months postpartum.